EFEKTIVITAS PROMOSI KESEHATAN MELALUI MEDIA SOSIAL DALAM MENDORONG PERILAKU HIDUP SEHAT PADA REMAJA - Rabindra Aldyan Bintang Mustofa; Mutiara Sani (Sosial Simbiosis : Jurnal Integrasi Ilmu Sosial dan Politik, 2024)
This study aims to evaluate the effectiveness of health promotion through social media in encouraging healthy behaviors among adolescents. The discussion covers two main aspects: the urgency of health promotion through social media for adolescents, and the effectiveness and challenges faced in its implementation. The urgency of health promotion through social media is based on the high usage of digital platforms among adolescents, making it a potential tool for disseminating health information. Social media allows for quick and wide access to educational content, enhances health literacy, and encourages active participation of adolescents in maintaining their health. The study results indicate that health promotion through social media is effective in increasing health knowledge and motivating healthy behavior changes. However, several challenges need to be addressed, such as the spread of inaccurate information, limited access and digital literacy, and issues of privacy and data security. This study concludes that despite the challenges, social media has great potential as an effective health promotion tool for adolescents. Appropriate strategies are needed to overcome these challenges, including digital literacy education and the development of regulations to ensure information accuracy. Further research is recommended to explore the combination of social media with face-to-face interventions to enhance the effectiveness of health promotion